Caloric Content Has Greater Level Of Brain Activation During Carbohydrate Mouth Rinsing - Abu Bakar, Al-Hafiz (2017)
Mouth rinsing a carbohydrate (CHO) solution has been shown to activate receptors within the oral cavity which is related to reward and pleasure centres of the brain for the enhancement of endurance exercise performance. However, it remains unclear whether the caloric content or the sweetness level of a solution may influence the level of brain activation during mouth rinsing. Therefore, the aim of this study was to examine the influence of caloric content or the sweetness level on brain activation when performing CHO mouth rinsing. Eleven healthy male participants (Age: 20 ± 1 years; height: 168.7 ± 6.1 cm; body mass: 61.4 ± 6.1 kg; and peak rate of oxygen consumption (VO2max): 51.7 ± 2.5 mL.kg.min-1) volunteered for this study.